Should Financial Sector Regulators Be Independent? - Quintyn, Marc (Economic Issues; Economic Issues ;, 2004)
In nearly every major financial crisis of the past decade-from East Asia to Russia, Turkey, and Latin America-political interference in financial sector regulation helped make a bad situation worse. Political pressures not only weakened financial regulation, but also hindered regulators and supervisors from taking action against troubled banks. This paper investigates why, to fulfill their mandate to preserve financial sector stability, financial sector regulators and supervisors need to be independent-from the financial services industry as well as from the government-as well as accountable.